2017
DOI: 10.21614/jpss.11.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Blunt Abdominal Trauma- Demography in a Tertiary Care Set Up of a Developing Nation

Abstract: Purpose: Pediatric patients represent nearly 10 percent of all trauma admissions in major trauma centers. The study attempts to study the different patterns of demography in patients suffering from trauma to the abdomen in a tertiary care hospital in a developing nation. Methods: The study was done in a tertiary care center over a duration of one year. The study was retrospective based on hospital records of the patients. The demographic parameters were studied and compared to available literature. Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, in a study, surgical intervention was required for 50% of splenic injuries, 44% of liver injuries, 25% of pancreatic injuries, and 23% of renal injuries. This is higher than numerous findings, such as those by Ghosh et al 14 About 6% of patients had gastrointestinal (GI) perforations, and 25% of patients required surgical intervention. In similar study large gut perforation was found in 3.5% of cases, bile duct injury (1.4%) and small gut perforation (2.1%).…”
Section: Discussionmentioning
confidence: 59%
“…However, in a study, surgical intervention was required for 50% of splenic injuries, 44% of liver injuries, 25% of pancreatic injuries, and 23% of renal injuries. This is higher than numerous findings, such as those by Ghosh et al 14 About 6% of patients had gastrointestinal (GI) perforations, and 25% of patients required surgical intervention. In similar study large gut perforation was found in 3.5% of cases, bile duct injury (1.4%) and small gut perforation (2.1%).…”
Section: Discussionmentioning
confidence: 59%